Comparison of sCO2 and He Brayton cycles integration in a Calcium-Looping for Concentrated Solar Power. (15th May 2022) - Tesio, U.; Guelpa, E.; Verda, V.
Abstract: Concentrated Solar Power is expected to play a crucial role to reach a sustainable power generation. Efficiency increase and development of long-term storages are the main aspects that could be further addressed to enhance the Concentrated Solar Power diffusion. In this context, the Calcium-Looping process is a promising opportunity for the ThermoChemical Energy Storage. Previous studies showed that, between the indirect integrations, Brayton cycles operating with supercritical CO2 or Helium are an interesting alternative. However, since their discussion has been developed in separate works, a detailed comparison of these integrations is lacking. The purpose of the present study is to find the differences, similarities and important aspects that characterize the two systems, performing a comparison in energy, economic and technical terms. Results show that choosing the He power block allows to reach the highest performances, while the cheapest alternative is the sCO2 cycle. Compression, regeneration, and high-temperature heating are the most important aspects for the He integration, differently from the case with sCO2, where only the regeneration process determines changes of the plant benchmarks. The comparison does not highlight univocally a better option, but according to the criteria required is possible to evaluate the most suitable alternative. Highlights: Calcium-Looping as Thermochemical energy storage for Concentrated Solar Power. Comparison between He and sCO2 Brayton integrations with multiobjective approach. A composite Pareto curve is obtained. He indirect integration results more efficient, while the sCO2 alternative is cheaper. Analysis and comparison of components' costs, sections' costs and energy losses.